PENGARUH EDUKASI RASIONALISASI ANTIBIOTIK TERHADAP PENGETAHUAN MASYARAKAT DI DESA SUNGAI LANANG - armayanti, dini; Khutami, Chindiana; Pratama, Septa (Jurnal Penelitian Farmasi Dan Herbal, 2026)
Irrational use of antibiotics contributes to the increasing incidence of antimicrobial resistance (AMR). Limited public knowledge regarding the indications and proper use of antibiotics leads to inappropriate usage. This study aimed to determine the level of community knowledge before and after educational intervention and to analyze the effect of education on improving knowledge among residents of Dusun III, Sungai Lanang Village. This study employed a pre-experimental one group pretest–posttest design involving 71 respondents selected through purposive sampling from a population of 245 individuals. Data were collected using a questionnaire that had been tested for validity and reliability. Statistical analysis was performed using the Wilcoxon Signed Ranks Test because the data were not normally distributed (p < 0.05). The results showed that prior to the educational intervention, the majority of respondents had poor knowledge (59%), whereas after the intervention, most respondents were categorized as having good knowledge (70%). The Wilcoxon test result showed p = 0.000 (p < 0.05), indicating a significant effect of education on improving knowledge. In conclusion, antibiotic rationalization education is effective in increasing community knowledge and should be implemented continuously to prevent antibiotic misuse.